Development and Management Model of Podcast Media Evaluation in Improving Reading Skills - Ahmad Zarkasyi (STAI Syaichona Moh. Cholil Bangkalan, 2024)
This article describes the development and management model of podcast media evaluation in improving reading skills at the Miftahul Ulum Islamic Boarding School in Lumajang Regency. This study uses a qualitative approach with a case study approach. Data collection uses in-depth interviews, participatory observation, and documentation. Data analysis uses the stages of data condensation, data presentation, and concluding. The results of the study indicate that the development and management model of podcast media evaluation for learning in improving the ability to read books without punctuation at the Miftahul Ulum Islamic Boarding School is assisted by expert assessors of material media and subject teachers related to aspects of planning, presentation, language, and language material.